PENGARUH LATIHAN KECEPATAN THE LOOP TERHADAP KETERAMPILAN MENGGIRING BOLA SISWA SSB PTPN V PEKANBARU - Pamungkas, Rizky; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is the speed of PTPN V Pekanbaru SSB students when dribbling is still not optimal, students still look slow in dribbling so students have difficulty in dribbling the ball to attack or when chasing opponents when defending. The purpose of this study was to determine the effect of the loop speed training on the dribbling skills of SSPN PTPN V Pekanbaru students. The population in this research were 14 students of PTPN V Pekanbaru SSB. In the research the sampling technique used was total sampling, so the sample in this study was 14 students of PTPN V Pekanbaru SSB. The instruments used to collect data are pre test and post dribbling test. The data analysis technique used is the t test. From the results of normality test data of pre-test and post-test dribbling skills of SSB students of PTPN V Pekanbaru, it was obtained that Lhitung pree test was 0.143 and Lhitung post test was 0.133 with Ltable value according to the number of samples of 14 people was 0.227. so Ltable> Lhitung or 0.227> 0.143 and> 0.133 so that it can be said that the data is normally distributed. Based on the results of the t test, obtained t count = 9,944> t table = 1,771. So it can be concluded that there is an influence of the loop speed training on the dribbling skills of SSPN PTPN V Pekanbaru students.Key Words: Speed Loop Training, Dribbling Skills